Weakly associated water in biological objects and at silica interfaces - Gun'ko, V. M.; Turanskaya, S. P.; Nechipor, O. V.; Yukhimenko, E. V.; Goncharuk, E. V.; Turov, V. V.; Chuiko, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2006)
The behaviour of water at mosaic hydrophilic/hydrophobic surfaces of different silicas and in biosystems (biomacromolecules, yeast cells, wheat seeds, bone and muscular tissues) was studied in different dispersion media over wide temperature range using 1H NMR spectroscopy with layer-by-layer freezing-out of bulk water (close to 273 K) and interfacial water (180 < T < 273 K), and quantum chemical methods. Bulk water and water bound to hydrophilic/hydrophobic interfaces can be assigned to different structural types. There are (i) weakly associated interfacial water (1H NMR chemical shift dH = 1.1-1.7 ppm) that can be assigned to high-density water (HDW) with collapsed structure (CS), representing individual molecules in hydrophobic pockets, small clusters and interstitial water with strongly distorted hydrogen bonds or without them, and (ii) strongly associated interfacial water (dH = 4-5 ppm) with larger clusters, nano- and microdomains, and continuous interfacial layer with both HDW and low-density water (LDW). The molecular mobility of weakly associated bound water is higher (because hydrogen bonds are distorted and weakened and their number is smaller than that for strongly associated water) than that of strongly associated bound water (with strong hydrogen bonds but nevertheless weaker than that in ice Ih) that results in the difference in the temperature dependences of the 1H NMR spectra at T < 273 K.